Variasi Laju Pemakanan Bahan Bakar RDF Terhadap Distribusi Temperatur Dual Reaktor Fluidized Bed - Septiawan, Anhar; Winaya, I Nyoman Suprapta; Darma, I Wayan Arya (Teknik Desain Mekanika, 2024)
Abstractt This research was conducted to determine the effect of the fuel feeding rate of RDF on the temperature distribution in a dual reactor fluidized bed, which is used to overcome current energy problems. the method used in this research is experimental method. The results obtained in this study are the higher the fuel feeding rate used, the lower the gasification temperature distribution in the dual reactor fluidized bed device. The temperature distribution in the gasification reactor has decreased due to an endothermic reaction, while the temperature in the combustion reactor has increased due to the exothermic reaction and will decrease over time due to the supply of free air from the blower and compressor. The free air functions to fluidize the fuel and also the bed materia. Keyword : Gasification, Dual Reactor Fluidized Bed, Fuel Feeding Rate